Efficacy analysis of the Tendvia™ pulmonary artery stent thrombectomy system in the treatment of intermediate- to high-risk pulmonary embolism - Lu, Xunlai; Liu, Shengfu; Chen, Changmei; Chen, Junwen; Xu, Shenrui; Luo, Yuanjia; Luo, Jiachao (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo investigate the clinical efficacy of the Tendvia™ pulmonary artery stent thrombectomy system in treating patients with intermediate-high risk and high-risk acute pulmonary embolism.MethodsA total of 15 consecutive patients with acute pulmonary embolism (classified as intermediate-high risk and high risk) admitted to Northeast Yunnan Central Hospital from January 2025 to March 2025 were enrolled. Among them, there were 7 male and 8 female patients, with a mean age of (65.2 ± 11.38) years. All patients underwent percutaneous mechanical thrombectomy (PMT) using the Tendvia™ pulmonary artery stent thrombectomy system. General patient information, including history of venous thromboembolism (VTE), surgical history within four weeks, and embolism locations, was recorded. Changes in pulmonary artery pressure before and after thrombectomy, as well as preoperative and postoperative ratios of right ventricular diameter to left ventricular diameter (RV/LV) on echocardiography, and relevant results from biochemical tests such as troponin, D-dimer, and N-terminal pro-B-type Natriuretic Peptide (NT-BNP), were compared. The improvement in right heart function, hemodynamic changes, and alterations in myocardial enzymes were evaluated to assess the safety and efficacy of the Tendvia™ pulmonary artery stent thrombectomy system.ResultsThe surgical procedures were effective in all 15 patients, with no mortality reported. Pulmonary artery pressure significantly decreased after thrombectomy compared to preoperative levels, demonstrating statistical significance. Symptoms such as chest tightness, chest pain, and dyspnea were markedly alleviated in all patients.ConclusionThe Tendvia™ pulmonary artery stent thrombectomy system demonstrates definitive efficacy in treating intermediate-high risk and high-risk pulmonary embolism, with a low incidence of surgical complications.